Kinetic Model for Denitration Reaction Process of Cylindrical Single-Base Gun Propellant - Cui, Fan; Fan, Hong-Lei; Li, Shi-Ying; Wu, Xiao-Qing; Li, Chun-Zhi; Xiao, Zhong-Liang (ACS omega, 2023)
As a new type of progressive energy release propellant, nitro gradiently distributed propellant (NGDP) was prepared by a denitration reaction between a denitration reagent and the propellant to remove the energy-containing functional group (-O-NO ) from the surface of the propellant. The kinetics of the denitration reaction determines distribution of the nitrate group in the surface layer of NGDP, which further affects the combustion progressivity. In this paper, the kinetic model for the denitration reaction process of the cylindrical single-base gun propellant was studied by the shrinking unreacted core model (SUC model). The energy change of the propellant particles before and after the denitration reaction was used to evaluate the denitration rates, which were used to fit the proposed SUC cylindrical model. The results show that the rate-controlling step of the denitration reaction process is largely dependent on the concentration of the denitration reagent. At low concentrations (the concentration of the denitration reagent was 6%), the denitration reaction process was controlled by the chemical reaction, and the activation energy was found to be 48.40 kJ·mol . When the concentration increased (the concentration of the denitration reagent was 15%), the rate-controlling step changed to a solid product layer diffusion control with an activation energy of 84.77 kJ·mol . The kinetic models obtained in this study can provide theoretical guidance for the controlled preparation of NGDP with good combustion progressivity.